MEDICATION ADHERENCE RELATIONSHIP WITH RELAPSE IN PATIENTS WITH HALLUCINATIONS POLYCLINIC IN MENTAL HOSPITAL Prof. Dr. SOEROJO MAGELANG - Rosi Fahmilia; Suwarno .; Witriyani . (STIKES DUTAGAMA KLATEN, 2014)
Background: Mental health is one of the four major health problem in developed countries, although the problem is not considered a mental health disorder that causes death directly, but the disorder can lead to the inability of individuals to behave that can inhibit development because they are not productive (Hawari, 2009). Purpose: The purpose of the study to Know medication adherence relationship with relapse in patients with hallucinations in Polyclinic Hospital Mental Prof. Dr.. Soerojo Magelang. Method: The study was a descriptive correlation study, with cross design sectional.research time held in November 2012-August 2013, the population in this study were 210 patients hallucinations. sampling techniques by mean of disproportionate stratified random sampling with 61 correspondents in accordance with inclusion criteria. Results: There was no significant between medication adherence relationship with relapse in patients with hallucinations, a score of 10.676 X2 count. Price X2 with df = 1 for 3,841 then X2 count is greater than the X2 table (10.676> 3.841) and P-value = 0.001 is less than the value of alpha (α = 0.05) which means that the alternative hypothesis (Ha) is accepted that there medication adherence relationship with relapse in patients with hallucinations. Conclusion: There was a significant between medication adherence relationship with relapse in patients with hallucinations. Good medication adherence would reduce the risk of relapse in patients with hallucinations.